Analysis of guinea pig leukocyte antigens using interspecies T cell hybrids - Schäfer, Hubert; Müller, Beate; Bader, A.; Schenkel, Johannes; Burger, Reinhard (Journal of immunological methods, 1989)
In the guinea pig system, there are no T lymphocyte tumors available. In addition, in this species the production of T cell lines in vitro for analysis of T cell markers or function proved to be difficult. As an alternative approach, guinea pig X mouse and guinea pig X rat T cell hybridomas were obtained by fusion of guinea pig T cells with HAT-sensitive mouse or rat thymomas. In ten fusions a total of 578 hybrids were produced and kept in culture for periods ranging from weeks up to several months. The highest yield was obtained when the Mb C 12 line was used as tumor parent. BW 5147 and the rat thymoma W/Fu(C58NT)D gave slightly lower fusion efficiencies. The yield depended also on the pretreatment of the parental cells. Activation by MLR proved to be most effective. A number of interspecies hybrids expressed guinea pig T cell differentiation antigens as detected by a cell ELISA. The positive hybrids were recloned several times and exhibited a stable expression of these markers, even after continuous culture for more than 2 months. Western blot analysis was used to confirm antigen expression at the protein level by comparing the hybrids with both parental cells. The hybrids expressed the proteins of the guinea pig lineage. No reaction was observed with the murine or rat thymomas. Therefore, the application of interspecies T cell hybrids provides an alternative for studies of guinea pig T cells. The cells are easy to grow and to clone and may be stored frozen in liquid nitrogen. The hybrids should permit analysis at the clonal level also for functional studies.
Available online: 11 November 2002
Gesehen am 05.03.2021